A Defect Evaluation Methodology Based on Multiple Magnetic Flux Leakage (MFL) Testing Signal Eigenvalues. Issue 1 (2nd January 2016) - Sun, Yanhua; Liu, Shiwei; Ye, Zhijian; Chen, Shaobo; Zhou, Qian
Abstract : This article is based on the associated linearity of magnetic flux leakage signal eigenvalues and detection status information, proposing a methodology that applies multiple magnetic flux leakage signal eigenvalues to evaluate defects and goes a step further in conforming the limitation of the traditional evaluation system, which merely uses signal peak values. In response to the situation that magnetic flux leakage testing signal peak values have been applied as the main parameters to evaluate defects and carry out various related research, we find that the single magnetic flux leakage testing signal peak values cannot exactly represent the leakage magnetic field and reflect the information of the defects. So we attempt to come up with a new way of defects evaluation to better and more accurately evaluate defects. By means of simulation analysis in simulation software ANSYS and experimental verification, the linear relationships between multiple magnetic flux leakage signal eigenvalues and defect parameters through which we can exactly evaluate the defects are obtained, respectively. Finally, the validity of this evaluation system is firmly demonstrated by a practical defect.